Computer aided design (CAD) and modelling in railway engineering technology - Mahyeddin, Mohd Eizzuddin; Abd Latif, Muhamad Faiz; Osman, Mohd Hairi (Penerbit UTHM, 2020)
Computer aided design (CAD) is the use of computers (or workstation) to aid in the creation, modification, analysis, or optimization of a design. CAD software is used to increase the productivity of the designer, improve the quality of design, improve communications through documentation, and to create a database for manufacturing..